Legal Disharmony and Disaster Risks: Ecological Sovereignty Restoration Through the Indigenous Peoples Bill - Ahmad Wasito (Peradaban Journal of Law and Society, 2025)
The escalation of hydrometeorological disasters in the upstream regions of Sumatra reflects a systemic failure in forestry governance, which is increasingly ensnared in an extractive paradigm. This article aims to analyze the correlation between regulatory disharmony and the rising risk of ecological disasters, while repositioning the Indigenous Peoples Bill as a preventive judicial instrument within the national disaster mitigation framework. Utilizing a normative legal research approach through a discourse analysis of sectoral regulations and policies, this study demonstrates that regulatory fragmentation—particularly following the implementation of the Job Creation Law—has precipitated an "administrative disaster" characterized by the legalization of forest area violations and the removal of ecological protection thresholds in upstream regions. Such conditions create a zone of impunity that systemically undermines the role of indigenous communities as guardians of the upstream ecosystem. This article argues that the Indigenous Peoples Bill serves as a crucial legal unification mechanism to resolve the implementation deadlock of the Constitutional Court Decision No. 35/PUU-X/2012 while simultaneously ending management dualism in upstream areas. Consequently, the recognition of customary land rights is not merely a human rights issue, but a fundamental legal prerequisite for public safety and the restoration of national ecological sovereignty. Eskalasi bencana hidrometeorologi di wilayah hulu Sumatra merefleksikan kegagalan sistemik tata kelola kehutanan yang semakin terperangkap dalam paradigma ekstraktif. Artikel ini bertujuan menganalisis hubungan antara disharmoni peraturan perundang-undangan dengan meningkatnya risiko bencana ekologis, serta mereposisi RUU Masyarakat Adat sebagai instrumen yuridis preventif dalam mitigasi bencana nasional. Dengan menggunakan pendekatan penelitian hukum normatif melalui analisis diskursus regulasi dan kebijakan sektoral, kajian ini menunjukkan bahwa fragmentasi regulasi—terutama pasca-implementasi UU Cipta Kerja—telah melahirkan “bencana administratif” berupa pemutihan pelanggaran kawasan hutan dan penghapusan ambang batas perlindungan ekologis wilayah hulu. Kondisi tersebut menciptakan zona impunitas yang secara sistemik melemahkan peran masyarakat adat sebagai penjaga ekosistem hulu. Artikel ini berargumen bahwa RUU Masyarakat Adat berfungsi sebagai mekanisme unifikasi hukum yang krusial untuk mengatasi kebuntuan implementasi Putusan Mahkamah Konstitusi No. 35/PUU-X/2012 sekaligus mengakhiri dualisme pengelolaan kawasan hulu. Dengan demikian, pengakuan hak ulayat tidak semata merupakan isu hak asasi manusia, melainkan prasyarat yuridis bagi keselamatan publik dan pemulihan kedaulatan ekologis nasional.